2010
DOI: 10.4269/ajtmh.2010.09-0688
|View full text |Cite
|
Sign up to set email alerts
|

Acute Arboviral Infections in Guinea, West Africa, 2006

Abstract: Acute febrile illnesses comprise the majority of the human disease burden in sub-Saharan Africa. We hypothesized that arboviruses comprised a considerable proportion of undiagnosed febrile illnesses in Guinea and sought to determine the frequency of arboviral disease in two hospitals there. Using a standard case definition, 47 suspected cases were detected in approximately 4 months. Immunoglobulin M antibody capture enzyme-linked immunosorbent assays and plaque-reduction neutralization assays revealed that 63%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 34 publications
(23 reference statements)
2
37
0
Order By: Relevance
“…The TAHV IgG titers detected in the current study were over 4-fold higher than those of the other studied orthobunyaviruses in the California serogroup (INKV and CHATV). This is consistent with the view that TAHV is widespread in Europe, 30 Russia, 31 Africa, [32][33][34][35] and Asia (southern Siberia and the Far East, Turkey, Armenia, Azerbaijan, Tadjikistan, Uzbekistan, and China), 30,[36][37][38] whereas INKV and CHATV may be restricted to northern Europe and Asia. 2,30,39 In the endemic region of Europe, approximately 5% of the general population are seropositive for TAHV, 40 and very high frequency (60-80%) of neutralizing antibodies have been reported in elderly persons in the endemic foci.…”
Section: Discussionsupporting
confidence: 76%
“…The TAHV IgG titers detected in the current study were over 4-fold higher than those of the other studied orthobunyaviruses in the California serogroup (INKV and CHATV). This is consistent with the view that TAHV is widespread in Europe, 30 Russia, 31 Africa, [32][33][34][35] and Asia (southern Siberia and the Far East, Turkey, Armenia, Azerbaijan, Tadjikistan, Uzbekistan, and China), 30,[36][37][38] whereas INKV and CHATV may be restricted to northern Europe and Asia. 2,30,39 In the endemic region of Europe, approximately 5% of the general population are seropositive for TAHV, 40 and very high frequency (60-80%) of neutralizing antibodies have been reported in elderly persons in the endemic foci.…”
Section: Discussionsupporting
confidence: 76%
“…10 Furthermore, a number of studies indicates CHIKV circulation in Kenya and Cameroon during interepidemic periods. [11][12][13] Circulation of CHIKV has also been reported in a few West African countries: it has been described in a cluster of travelers returning from Senegal with active CHIKV infection 14 and acute cases of CHIKV-related disease were detected in Guinea 15 and likely, Sierra Leone. 16 Furthermore, a recent study reported a seroprevalence of 46% for CHIKV-specific immunoglobulin G (IgG) in hospitalized patients in Nigeria during 2008.…”
mentioning
confidence: 99%
“…Moreover, because most CHIKV studies in Africa have been conducted during epidemics, little is known about virus circulation among humans between outbreaks. A study in West Africa with 47 participants found four with serologically confirmed acute CHIKV infection during a nonepidemic period, 10 suggesting that the virus may continue to be transmitted to humans between outbreaks. To our knowledge no such study has been conducted in East Africa.…”
Section: Introductionmentioning
confidence: 99%